The Influence of Multicultural Leadership and Teacher Professionalism on the Performance of Junior High School Teachers - Soraya, Evitha; Supadi (Journal of Education Reseach and Evaluation, 2023)
The principal’s role is so significant in achieving educational goals that the quality of the principal largely determines the success or failure of a school, especially his ability to empower teachers and employees toward a conducive working atmosphere. The research was conducted to analyze the influence of multicultural Leadership from school principals and teacher professionalism on the performance of junior high school teachers. The research used quantitative and qualitative methods with the Sequential Explanatory design method (sequence of proof). In contrast, the research data came from 110 teachers who teach in 44 public junior high schools. Primary data sources are obtained from interviews, observations, and documentation of research objects to support qualitative research analysis. Secondary data comes from documents and school reports related to teacher performance. The study's results indicate a positive influence of multicultural Leadership on improving teacher performance, a positive influence of professionalism on teacher performance, and a significant positive relationship between the principal leadership and teacher professionalism on teacher performance. The implications of the research results show how important the role of school principal leadership is in increasing teacher professionalism which in turn can improve teacher performance.